6 - L’Efficacité externe et l’équité d’accomplissement des diplômés sénégalais de l’enseignement technique supérieur - Fadiga Maïmouna; De Ketele, Jean-Marie (Journal of Higher Education in Africa, 2006)
This research is a study on the evaluation of the external efficiency and achievement of Senegalese graduates from the École Normale Supérieure d’Enseignement Tech- nique et Professionnel (ENSETP), a national technical training school, from 1981 to 1994. Despite notable dysfunction in the educational systems of most African countries, technical teaching and vocational training seem, however, to be a solu- tion to social and economic development. It is in this perspective that the Dakar- based ENSETP was set up in October 1976, in order to train trainers specialised in technical teaching and vocational training. However, the whole context of Structu- ral Adjustment Programmes (SAPs) and liberalisation came to question this impetus, since the ENSETP graduates (just like most graduates from a number of training schools) who used to be recruited in public administration, were no longer employed since 1995. The purpose of this study is therefore to reflect, through a retrospective and longitudinal study, on the relationship between the training given at ENSETP and its influence on the Senegalese social and economic environment. Our aim is to see whether the training provided at ENSETP (and the qualifications awarded) are beneficial to their holders, from a cognitive, social, professional, personal etc. point of view, in such a way that allow them to contribute to the economic and social development of the country. The interest of this work is in its qualitative approach. It has thus helped define qualitative indicators that allow for an evaluation of the quality of the human resources and that could help improve the decision-making process.